Digital Financial Technologies as Drivers of Inclusive Growth: A Strategic Review of Pakistan’s Fintech Landscape - Iqbal, Javed; Noman, Muhammad (Journal of Business and Economic Options, 2025)
Fintech has changed the way traditional banking and financial service delivery are done, offering a number of fresh, innovative solutions to the problem. This article explores how financial technologies have led to better economic development in Pakistan when it comes to delivering financial services. It also investigates in particular for people living in remote or underserved areas how well off they can be served by financial technology. Since levels of financial inclusion in Pakistan are rather low, there is the potential for fintech to be a catalyst to make finance more inclusive and to drive system upgrades. The study is using a sophisticated evaluation technique for fintech's application in Pakistan's problems and will supply a set of strategies as well as policy recommendations. Technologies such as digital banking platforms, online payment systems, micro-finance technologies, and other new forms of lending--advising services that can be automated have great potential to reduce the cost for financial service delivery so it is lighter on the consumer's wallet. Looking at the existing environment of fintech reveals significant barriers--a lack of regulation, digitally illiterate populations and insufficient infrastructure. Despite its potential as a mainstream phenomenon, conformed to Pakistan's particular circumstances through policy recommendations from research findings, this paper offers a systematic analysis of the state of the literature and secondary data. It also draws lessons from countries where fintech has been successfully integrated and looks at how best such combinations can be applied here. Overall, this study helps further illuminate the role of fintech in Pakistan and presents opportunities worth exploring for digital financial solutions, which are both a sustainable form of economic development and well-adapted to Pakistan's conditions.